The Influence of Comic Media in the Team Games Tournament (TGT) Model to Improve Science Literacy in Elementary School Class III Animal Life Cycle Materials - Huqqat Inayatul Khairi; Wati Sukmawati (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of using comic media in the Team Games Tournament (TGT) learning model on improving the science literacy of elementary school students on the topic of animal life cycle. Science literacy is an essential skill that should be fostered from an early age. This quantitative study employed a quasi-experimental pretest-posttest control group design involving 48 third-grade students at SDN Duren Tiga 13, South Jakarta, divided into an experimental class (21 students) and control class (27 class). A 25 item multiple choice instrument was used, analyzed using the Rasch model via the Winstep application. Results showed that 20 out 21 students (95.24%) in experimental goup improved, while only 1 declined. In contrast, only 18 of 27 students (66.70%) in control class improved, with 4 remaining unchanged and 5 declining. An Independent sample t-test confirmed a significant difference between the groups, t(46) = 2.973, p = 0.005. these findings indicate that integrating comic media with the TGT model learning effectively enhance students’ science literacy and may serve as an engaging alternative to conventional instruction.